The Role of Organizational Governance in Enhancing Accountability and Performance in Government Agencies - Ananda Saputri; Yuliana; Lestari (Yayasan Cinta Negara Indonesia, 2026)
Good organizational governance is a key factor in improving the accountability and performance of government agencies. The application of governance principles including transparency, accountability, responsibility, independence, and fairness is expected to strengthen the effectiveness of government administration and enhance public trust in the services provided. This study aims to analyze the role of organizational governance in improving the accountability and performance of government agencies. The research method used is a quantitative approach with data collection techniques involving the distribution of questionnaires to government officials in several government agencies. The data were analyzed using linear regression analysis to test the influence of organizational governance on the accountability and performance of government agencies. The results indicate that organizational governance has a positive and significant effect on the accountability of government agencies. Furthermore, organizational governance has also been shown to improve agency performance through more effective resource management, transparent decision-making, and the strengthening of internal control systems. Thus, the implementation of good organizational governance serves as a strategic instrument in achieving accountability and the sustainable improvement of government agency performance